2015
DOI: 10.1016/j.reprotox.2015.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deletion of the transcription factor Nrf2 and benzo [a]pyrene treatment on ovarian follicles and ovarian surface epithelial cells in mice

Abstract: Polycyclic aromatic hydrocarbons, like benzo[a]pyrene (BaP), are ubiquitous environmental pollutants and potent ovarian toxicants. The transcription factor NRF2 is an important regulator of the cellular response to electrophilic toxicants like BaP and to oxidative stress. NRF2 regulates transcription of genes involved in the detoxification of reactive metabolites of BaP and reactive oxygen species. We therefore hypothesized that Nrf2−/− mice have accelerated ovarian aging and increased sensitivity to the ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…A previous study showed that the inhibition of Nrf2 increased B[a]P toxicity and decreased the expression of several GSTs [72]. To confirm that silymarin regulates the Nrf2 signaling pathway, which is related to the attenuation of BPDE-DNA adduct formation, we demonstrated that knockdown of Nrf2 expression by RNA interference abolishes the inhibition of BPDE-DNA adduct formation by silymarin ( Figure 5B).…”
Section: Discussionsupporting
confidence: 52%
“…A previous study showed that the inhibition of Nrf2 increased B[a]P toxicity and decreased the expression of several GSTs [72]. To confirm that silymarin regulates the Nrf2 signaling pathway, which is related to the attenuation of BPDE-DNA adduct formation, we demonstrated that knockdown of Nrf2 expression by RNA interference abolishes the inhibition of BPDE-DNA adduct formation by silymarin ( Figure 5B).…”
Section: Discussionsupporting
confidence: 52%
“…We assume that in order to avoid B[a]P-induced toxicity, the low level of ROS molecules activates signaling networks such as transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) hypoxia-inducible factor (HIF)1α and nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB), which are involved in maintaining cell homeostasis 43 , 44 . Once activated, Nrf2 binds to antioxidant response elements (ARE) of antioxidant genes including genes for NADPH production, glutathione homeostasis/utilization and of phase I and II enzymes 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor NRF2 stimulates the expression of detoxifying and antioxidant genes thus preserving the homeostasis of the primordial follicle pool. Indeed, null Nrf2 mice exposed to the toxicant benzo-a-pyrene (BaP) display an accelerated ovarian follicle depletion by middle-age [ 89 ]. The rate-limiting step of GSH synthesis is catalyzed by the heterodimeric enzyme glutamate cysteine ligase, composed of a modifier ( Gclm ) and a catalytic ( Gclc ) subunit.…”
Section: Origin Of Female Cancersmentioning
confidence: 99%